A novel coating method using zinc oxide nanorods to improve the interfacial shear strength between carbon fiber and a thermoplastic matrix. (6th October 2016) - Song, Seung A.; Lee, Choong Kwang; Bang, Yun Hyuk; Kim, Seong Su
Abstract: The interfacial shear strength between the fiber and the thermoplastic matrix is one of the most important factors affected mechanical performances of carbon fiber-reinforced thermoplastic composites (CFRTPs). There have been many investigations of the interfacial shear strength that studied surface treatments. Chemical treatment methods have been widely used to activate the inert fiber surface and thus increase the surface free energy. However, these treatment methods can degrade the mechanical properties of the carbon fibers due to surface etching. Coating metal oxides onto the carbon fibers using hydrothermal methods can improve the interfacial shear strength without degrading the mechanical properties of the fiber. However, due to their long processing time, it is difficult to apply these hydrothermal methods to the continuous manufacturing process for carbon fibers. In this study, a novel method for coating zinc oxide (ZnO) nanorods (NRs) onto the carbon fibers in a short time was investigated, which enhanced the interfacial shear strength with polypropylene without significant damage on the reinforcing fibers. An electrochemical deposition method (EDM) and a microwave radiation method were applied to create a uniform ZnO seed layer on the carbon fiber surface, and then the ZnO NRs were more densely and uniformly grown on the fiber surface by a direct heating method by applying microwave radiation for 10 min. The overall preparation time to grow ZnO NRs was decreased by 95.8%, and these novel methods effectively improved the interfacial shear strength of the CFRTP.